Self-reported reasons for on-duty sleepiness among commercial airline pilots. (2nd September 2021) - Sallinen, Mikael; Onninen, Jussi; Ketola, Kimmo; Puttonen, Sampsa; Tuori, Antti; Virkkala, Jussi; Åkerstedt, Torbjörn
ABSTRACT: Experimental and epidemiological research has shown that human sleepiness is determined especially by the circadian and homeostatic processes. The present field study examined which work-related factors airline pilots perceive as causing on-duty sleepiness during short-haul and long-haul flights. In addition, the association between the perceived reasons for sleepiness and actual sleepiness levels was examined, as well as the association between reporting inadequate sleep causing sleepiness and actual sleep-wake history. The study sample consisted of 29 long-haul (LH) pilots, 28 short-haul (SH) pilots, and 29 mixed fleet pilots (flying both SH and LH flights), each of whom participated in a 2-month field measurement period, yielding a total of 765 SH and 494 LH flight duty periods (FDPs) for analyses (FDP, a period between the start of a duty and the end of the last flight of that duty). The self-reports of sleepiness inducers were collected at the end of each FDP by an electronic select menu. On-duty sleepiness was rated at each flight phase by the Karolinska Sleepiness Scale (KSS). The sleep-wake data was collected by a diary and actigraph. The results showed that "FDP timing" and "inadequate sleep" were the most frequently reported reasons for on-duty sleepiness out of the seven options provided, regardless of FDP type (SH, LH). Reporting these reasons significantly increased the odds of increased on-duty sleepiness (KSS ≥ 7), except for reporting "inadequate sleep" during LH FDPs. Reporting "inadequate sleep" was also associated with increased odds of a reduced sleep-wake ratio (total sleep time/amount of wakefulness ≤ 0.33). Both "FDP timing" and "inadequate sleep" were most frequently reported during early morning and night FDPs, whereas the other options showed no such phenomenon. The present study suggests that airline pilots' perceptions of work-related factors that make them sleepy at work are in line with the previous experimental and epidemiological studies of sleepiness regulation.